The Role of GATA3 in Breast Cancer: An Updated Review - Yang, Jing; Zhao, Xu; Huang, Ruoyu; Zhao, Juanjuan; Guo, Mengmeng; Zhou, Ya; Xu, Lin (Current Chinese Science, 2021)
GATA binding protein 3 (GATA3), a member of the zinc finger-binding transcription factor GATA gene family, plays an important role in regulating the development and differentiation of various tissues and organs. Previous studies have manifested that GATA3 is implicated in inhibiting the development of breast cancer, including suppressing the growth, metastasis, and invasion of cancer cells. However, the exact role of GATA3 in breast cancer remains to be fully elucidated. Interestingly, recent studies have further shown that GATA3 can regulate a variety of new target genes, including ectonucleoside triphosphate diphosphohydrolase 3 (ENTPD3), semaphorin 3B (SEMA3B), and microRNAs (miRNAs) to promote tumorigenesis, epithelial-mesenchymal transformation (EMT), and metastasis of breast cancer. Meanwhile, GATA3 mutations can affect the role of GATA3 in inhibiting the growth and metastasis of breast cancer cells, which indicates that GATA3 might be a promising target for breast cancer treatment. Undoubtedly, these new evidence further uncover the complexity of the GATA3/targets network in breast cancer development. In this article, we review related research progress and put forward some questions about the development of GATA3 in the future in order to be helpful for the understanding on the exact role of GATA3 in the progress of breast cancer and the development of related new clinical treatment strategies that will ultimately benefit the clinical outcome of breast cancer patients.
Keywords: transcriptional binding